Controle cooperativo do fluxo de potência de microrrede CC com uso de sistema de armazenamento de energia - Oliveira, Gabriel Pereira de (2020)
The growing global energy demand and the increasing social/political concern for the environment has driven the insertion of renewable energy sources (RESs) in the electrical power system (EPS), such as photovoltaic systems and wind generation systems. Generally, these sourcers are inserted in the EPS as distributed generation (DGs) systems in the new matrix energy model organized by microgrids (MGs). MGs are small-scale networks composed of sources based on DGs, electrical loads and energy storage systems (ESS). RESs are dependent on meteorological conditions which make it intermittent and stochastic. To provide the energy balance of these microgrids, it is necessary to integrate ESSs. Therefore, this work proposes a cooperative control strategy to regulate the power flow of a DC MG with an interconnected ESS. The proposed strategy coordinates the voltage control of the DC bus by Interlink CC (ILC) and by ESS, providing power smoothing. To decouple the control loops from the bus, a Gaussian inference function is used based on the information of the voltage deviation on the DC bus. The proposed technique is validated through digital simulations and experimental tests.